Surgical treatment of shape and position of the greater trochanter of the femur in children with hip joint pathology - Gromov, Artem; Korolkov, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Objective: To assess the results of correction of the shape and position of the greater trochanter of the femur (GTF) after surgical treatment of hip joint (HJ) pathology in children. Methods: A retrospective analysis of the results of surgical treatment of the GTF deformities in 70 children (46 boys and 24 girls) between 2 and 18 years old. The children were divided into several groups: 18 patients with deformities the GTF (pathological hip dislocation (PHD) and the consequences of osteomyelitis), 8 with avascular necrosis of the femoral head (ANFH), 33 with congenital hip dislocation and 11 with coxa vara. The results of the treatment were assessed in terms from 3 to 16 years with the help of clinical, biomechanical and radiological methods. Results: In 88.7 % of cases there was achieved an improvement in clinical, radiological, biomechanical marks characterizing the HJ state comparing to preoperative ones. So, the symptom of Trendelenburg disappeared or decreased, strength of the abductor muscles increased in average on 11–20 % in the cases of coxa vara and on 30-45% in cases of ANFH. Indicators statopodographic study had a clear tendency towards normalization. Radiographic characteristics of trochanteric component of the HJ were within normal limits for each patient. Based on the working classification of the deformations of the GTF developed a differentiated approach to surgical procedures on it was offered in view of multiplanar character, extent and rate of progression of deformation, as well as with etiological factor and age of the patients. The most favorable outcomes after 3 years or more after the operation were obtained in cases of ANFH and coxa vara, and the least favorable - in the group of children with consequences of inflammatory diseases. Conclusion: The diagnosis and correction of the shape and position of the GTF in children with pathology of the HJ deserves special attention, and the surgical treatment of these abnormalities allows you to get better anatomical and functional results.